Parent Scaffolding of Young Children When Engaged with Mobile Technology - Wood, Eileen; Petkovski, Marjan; De Pasquale, Domenica; Gottardo, Alexandra; Evans, Mary Ann; Savage, Robert S. (Frontiers in Psychology, 2016)
Shared parent-child experiences while engaged with an iPad™ were examined to determine if and then how parents interact with their children when using mobile digital devices. In total, 104 parent-child dyads participated in an observation session where parent-child interactions using the touchscreen tablet device were video recorded in order to observe first-hand the supports and exchanges between parent and child (age range 46.21- 75.9 months). Results indicate that parents provide a great deal of support to their children while interacting with the touchscreen tablet device including verbal, emotional-verbal, physical and emotional-physical supports. The types of support offered did not differ as a function of parent gender or experience with mobile devices (users versus non-users). Overall, parents rated their own experience engaging with the touchscreen tablet and that of their child’s positively. Additional survey measures assessed parents’ perceptions of their child’s technology use and attitudes regarding optimal ages and conditions for introducing and using technology. Most parents indicated a preference for very early introduction to mobile technologies. Implications of these findings are discussed.